2023
DOI: 10.21203/rs.3.rs-2599562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of standard T2-weighted turbo spin echo and volumetric interpolated breath-hold examination magnetic resonance imaging sequences in the assessment of articular process dysplasia in Pug dogs with thoracolumbar myelopathy

Abstract: Background: Retrospective study to compare the classification, as normal, hypoplastic or aplastic, of thoracic (T10-T13) caudal articular process (CAP) morphology in Pug dogs with a thoracolumbar myelopathy as normal, hypoplastic or aplastic, between T2 weighted Turbo Spin Echo (T2W-TSE) and Volumetric Interpolated Breath-hold Examination (VIBE) Magnetic Resonance Imaging (MRI) sequences, in comparison to Computed Tomography (CT). We hypothesised a stronger agreement for VIBE in comparison to T2W-TSE. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…This made it difficult to conclude a clear relationship between the presence of a specific vertebral condition and the conformation of SAD. Recently, it has been shown that MRI has a fair sensitivity for the identification of CAP dysplasia, particularly if using three‐dimensionally reconstructable volumetric interpolated breath‐hold examination (VIBE) sequences compared with traditional T2‐W 24 . Although CAP dysplasia was identified in some dogs in this study, given that CT is the gold standard for diagnosis of this condition and the VIBE sequence was not performed, this could have been missed.…”
Section: Discussionmentioning
confidence: 82%
“…This made it difficult to conclude a clear relationship between the presence of a specific vertebral condition and the conformation of SAD. Recently, it has been shown that MRI has a fair sensitivity for the identification of CAP dysplasia, particularly if using three‐dimensionally reconstructable volumetric interpolated breath‐hold examination (VIBE) sequences compared with traditional T2‐W 24 . Although CAP dysplasia was identified in some dogs in this study, given that CT is the gold standard for diagnosis of this condition and the VIBE sequence was not performed, this could have been missed.…”
Section: Discussionmentioning
confidence: 82%